The Development of a Pocketbook for Civic Education (PPKn) as an Effort to Enhance Understanding of the Value of Patriotism Among 10th Grade Students at SMA Negeri 12, Jambi City - Nuraini, Intan; Maulia, Siti Tiara; Hajri, Priazki (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study uses the Research and Development (R&D) method, aimed at determining the feasibility of the Civic Education (PPKn) pocketbook on the theme of patriotism, which includes a QR code and video examples of daily life application. The research design employed is ADDIE (Analyze, Design, Develop, Implement, and Evaluate). The subjects of this study are all students of class X E4 at SMA Negeri 12 Jambi, with small and large group trial implementations. The results of this study show the validity value from experts and teachers obtained using the Aiken index, which is V = 0.91, categorized as very valid. This indicates that the developed PPKn pocketbook on patriotism is feasible for use. The practicality of the developed PPKn pocketbook can be seen from the students' responses, with an average of 83%, categorized as very practical. Based on these data, it can be concluded that the developed PPKn pocketbook on the topics of Pancasila and the 1945 Constitution for 10th grade students is both highly valid and highly practical for use.